Personality and attachment to romantic partners - Marušić, Iris; Kamenov, Željka; Jelić, Margareta (2006)
Previous research has extensively documented the important role of attachment styles in adolescent and adult close relations. However, few studies aimed at mapping the adult attachment styles into the wider personality structure. This study explores the personality correlates of two attachment dimensions in romantic relations – anxiety and avoidance. For this purpose, modified Brennan's Inventory of experience in close relations (Kamenov and Jelić, 2003) and NEO PI-R measuring five personality dimensions (Costa and McCrae, 1992) were administered to the sample of 352 university students. Results have shown a variety of relations between two attachment dimensions and personality traits, both at the domain and facet level. Also, significant gender differences were found both for attachment and personality dimensions, with females scoring higher than males on attachment anxiety, neuroticism and openness. Due to the observed gender differences separate analyses were conducted for both sexes, and revealed somewhat different pattern of correlations for female and male students. Regression analyses demonstrated that attachment anxiety is predicted by high neuroticism, while attachment avoidance is predicted by low openness in both males and females. Furthermore, low agreeableness significantly contributes to the prediction of both anxiety and avoidance in female sample. Conscientiousness had positive contribution to attachment anxiety in males, but negative contribution to attachment avoidance in females.
ENG